Perancangan Board Infografis Gizi Anak untuk Meningkatkan Literasi Kesehatan di Kawasan Posyandu Melati Bitung: Designing a Child Nutrition Infographic Board to Improve Health Literacy in the Melati Bitung Integrated Health Post Area - Dewi Intan Kurnia; Jayanti, Eka Putri; Erdy Erlangga; Fitzy Satria; Raka Wibisana; Daffa Fadil Shobihan (Journal of Public Health Education, 2025)
Introduction: In Indonesia, child nutrition problems, particularly stunting, remain a major challenge in public health development. According to the World Health Organization (WHO, 2020), approximately 149.2 million children under the age of five experience developmental disorders, with 94% residing in low- and middle-income countries. Indonesia continues to face a relatively high prevalence of child developmental disorders, with 7.51% of children affected and an estimated 1–3% of children under five experiencing developmental delays. In Bitung Jaya Village, Tangerang, limited community nutrition literacy remains a significant concern, with nearly 40% of residents demonstrating insufficient knowledge and awareness regarding child nutrition. Barriers such as limited access to health information and low educational attainment further exacerbate this issue. Objectives: This study aims to design an effective child nutrition education infographic tailored to the needs of the Bitung Jaya Village community as a creative strategy to improve public knowledge and awareness of child nutrition. Methods: This study employed a mixed methods research design. Data were collected from mothers attending Posyandu Melati through surveys and observations, as well as from Posyandu-related information sources, to identify community needs, knowledge gaps, and appropriate content for infographic development. Results: The findings indicate that the majority of mothers had limited understanding of balanced child nutrition and stunting prevention. The development of child nutrition infographics, designed using simple language and visual elements and displayed on the Posyandu bulletin board, was considered appropriate and accessible for the community. The infographic design addressed key nutrition topics relevant to local needs and was perceived as an effective educational medium. Conclusion: The child nutrition infographic developed in this study demonstrates potential as an effective health education tool to improve community nutrition literacy in Bitung Jaya Village. The use of visually engaging and contextually relevant educational media can support Posyandu activities and contribute to efforts to prevent child nutrition problems, including stunting, at the community level.